Hpv8 reverses the transcriptional output in lrig1 positive cells to drive skin tumorigenesis - Syed, Adnan Shahzad; Marcuzzi, Gian Paolo; Miller-Lazić, Daliborka; Heß, Jochen; Hufbauer, Martin; Akgül, Baki (Cancers, 2022)
Simple summary: Human papillomavirus (HPV) of genus beta (betaHPV) infects cutaneous epithelia and contributes to skin carcinogenesis, particularly in immunosuppressed patients. The HPV8 transgenic mouse model serves as a model for betaHPV-induced skin tumorigenesis. These animals express the complete early genome region of HPV8 under the control of the keratin (K)-14 promoter (K14-HPV8-CER). Skin tumorigenesis in these mice is driven by Lrig1-positive stem cells. To understand the role of HPV8 gene expression in Lrig1+ keratinocytes, we determined the transcriptional network in K14-HPV8-CER skin tumours and compared it to the already known pattern in Lrig1 stem cells. We showed that HPV8 differentially regulates 397 cellular genes in skin tumours and subverts the expression pattern of 23 genes in Lrig1+ cells. This study identified gene targets of HPV8 and its upstream regulators, which may play an important role in HPV8 mediated skin tumorigenesis. K14-HPV8-CER transgenic mice express the complete early genome region of human papillomavirus type 8 (HPV8) and develop skin tumours attributed to the expansion of the Lrig1+ stem cell population. The correlation between HPV8-induced changes in transcriptional output in the stem cell compartment remains poorly understood. To further understand the oncogenic pathways underlying skin tumour formation we examined the gene expression network in skin tumours of K14-HPV8-CER mice and compared the differentially expressed genes (DEG) with those of the Lrig1-EGFP-ires-CreERT2 mice. Here, we report 397 DEGs in skin tumours of K14-HPV8-CER mice, of which 181 genes were up- and 216 were down-regulated. Gene ontology and KEGG pathway enrichment analyses suggest that the 397 DEGs are acting in signalling pathways known to be involved in skin homeostasis. Interestingly, we found that HPV8 early gene expression subverts the expression pattern of 23 cellular genes known to be expressed in Lrig1+ keratinocytes. Furthermore, we identified putative upstream regulating transcription factors as well as miRNAs in the control of these genes. These data provide strong evidence that HPV8 mediated transcriptional changes may contribute to skin tumorigenesis, offering new insights into the mechanism of HPV8 driven oncogenesis.
Gesehen am 29.06.2022